Palliating the escalated post-PDT tumor hypoxia with a dual cascade oxygenation nanocomplex. (March 2022) - Li, Ying; Wu, Chunjiao; Zhai, Yuewen; Han, Ran; Gu, Ruoyu; Ma, Yuying; Gao, Peng; Qian, Zhiyu; Gu, Yueqing; Li, Siwen
Highlights: Tumor microenvironment hypoxia becomes more severe after tumor photodynamic therapy. The dual cascade oxygenation strategy, with primary oxygenation enhancing photodynamic efficacy and secondary oxygenation alleviating the hypoxia in the hypoxic tumor microenvironment. Palliating the escalated post-PDT tumor hypoxia can modulate tumor microenvironment and rejuvenate cancer immunity. Abstract: Despite widespread researches engaging in optimizing the efficacy of PDT, the exacerbated hypoxia phenotype in the tumor tissue after PDT has always been neglected. Moreover, the ramifications of aggravated post-PDT hypoxia for tumor microenvironment (TME) have only been poorly investigated. Herein, we report a dual cascade oxygenation strategy with primary oxygenating to promote PDT and re-oxygenation to ameliorate post-PDT hypoxia. In this strategy, nanocomplex RDV@CP@Ce6 was synthesized, which consisted of red blood cell-derived vesicles (RDV) as the outer shell and CAT-PCL nano-assembly encapsulating with Ce6 as the inner core. Our results showed that RDV@CP@Ce6 amplified the PDT treatment through the first oxygenation and relieved tumor hypoxia by the second reoxygenation following PDT. On the other hand, the dual cascade oxygenation strategy also could effectively unleash the suppression onto the tumor immune microenvironment, which could further constrain tumor development and metastasis. In addition, RDV@CP@Ce6 also exhibited excellent biocompatibility and superior stability in vivo. This dual cascade oxygenation strategy may provide a promising and pragmatic platform for clinical applications.